AGRICULTURAL REFORMS (IN THE EXAMPLE OF SURKHONDARYO) - Shohida JUMAYEVA (Scholar Express Journal, 2023)
In this article, the process of economic reforms carried out in the field of animal husbandry in the Surkhan oasis, the increase in the number of cattle and poultry in all regions of our country, the importation of purebred cattle from Poland, Germany, Belarus, and Ukraine, where animal husbandry is developed, the effectiveness of the development of farm breeding, livestock the processes of registration of employment records and extensive reforms in the field of animal husbandry were explained to the engaged population.
Keywords: livestock farms; livestock productivity; cattle